Festividades religiosas e socialização em espaços rurais: o caso de Silveira Martins - RS - Lenz, Ana Carla (2020)
This dissertation carries out a dialogue about the festivals for the Patron Saints of the rural communities of Silveira Martins, RS. They acquire a character of analysis because they represent a time of breaking with everyday life, of effervescence, consumption, vanity, cooperation and competition. The study aimed to understand the dynamics of the festivals for the Patron Saints, interspersed with the permanences and changes promoted by migrants and their descendants. It is based on the relations existing in the parties and in the connections of the local population with the places of the municipality landscape, having as a basis of analysis the approaches of the qualitative method. The methodological procedures for obtaining the collection of information were: 1st bibliographic review on the concept of landscape, place and understandings about the ordinal variable: the parties for the Patron Saints (religious and community); 2nd exploratory research; 3rd elaboration of the instrument to guide the interviews; 4th field analysis; 5th tabulation and writing of the dissertation. Considering that Geography allows the analysis of the relationship between human groups and the environments occupied by them, this work went through the landscape formation of the municipality, the places that make up the landscape units: housing, work and faith and socialization that encompasses the others. The material and immaterial heritage printed in the landscape are the identity references of its population, the set formed by these elements reveals the social dynamics of the group that it owns and in the case of the silveirense community they are simultaneously displayed in the Festivals for the Patron Saints, which is why they attract external consumers. It was found that Silveira Martins was built by immigrants from agricultural regions in Italy and, at present, the descendants of the explorers, most of them remain in the countryside, but with practices aimed at agribusiness. Traditional knowledge and practices, especially gastronomic ones, are exalted at parties to foster memories and also to ratify the local cultural identity, constituted on the basis of Italian and Catholic culture, a hegemonic belief in spatiality.